2021
DOI: 10.1177/00336882211044860
|View full text |Cite
|
Sign up to set email alerts
|

Learning with Immersive Virtual Reality: An Exploratory Study of Chinese College Nursing Students

Abstract: As an emerging technology, virtual reality (VR) is now being used in education, particularly with STEM-related learning. However, as with all pedagogical innovation, there is a lack of empirical research on the application of VR in situations where students are using it with their second language (L2) and existing studies generally rely on the use of non-immersive VR tools. This paper is one step in a process of understanding the affordances and constraints of a fully immersive VR system in facilitating langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…This observation corroborates previous findings regarding the power of VR as the 'ultimate empathy machine' (Barbot & Kaufman, 2020). In addition, as with previous studies, there was evidence of the potential that VR has to decrease anxiety, particularly for public speaking (4,23), to facilitate critical thinking (10), and that students are less distracted (24). However, one study comparing VR and mobile apps (11) found that although VR scored highly for engagement it was not significantly different to mobile apps.…”
Section: Research Question 1: Psychological and Emotional Statessupporting
confidence: 90%
See 3 more Smart Citations
“…This observation corroborates previous findings regarding the power of VR as the 'ultimate empathy machine' (Barbot & Kaufman, 2020). In addition, as with previous studies, there was evidence of the potential that VR has to decrease anxiety, particularly for public speaking (4,23), to facilitate critical thinking (10), and that students are less distracted (24). However, one study comparing VR and mobile apps (11) found that although VR scored highly for engagement it was not significantly different to mobile apps.…”
Section: Research Question 1: Psychological and Emotional Statessupporting
confidence: 90%
“…The one exception (24) reported that students felt anxious using VR, although that could be explained by the fact that the specific VR application used was not interactive and communicative activities, which students said caused anxiety, were not carried out within the application itself. One consistent result, echoing the previous systematic reviews, is that VR is enjoyable and motivating for students (2,5,6,7,10,18,20,21,22,23) especially for students who may initially not be that interested in language learning or confident in their linguistic skills (5,6), although some researchers warned of the influence of the novelty effect of learning with a new fun tool (20,23). In addition, two studies also found evidence supporting the positive impact of VR on willingness to communicate (6,24) and learner autonomy (24).…”
Section: Research Question 1: Psychological and Emotional Statessupporting
confidence: 60%
See 2 more Smart Citations
“…It has been argued that this approach can lead to a greater variety in the design of learning activities and provide more opportunities for learners to use the language more spontaneously in order to express themselves (Hinkel, 2010; Klimova, 2014; Oxford, 2001). These are similar arguments and they dovetail into studies regarding the communicative potential of VR for language learning (Parmaxi, 2020; Tai et al, 2022; Uygun and Girgin, 2022).…”
Section: Introductionmentioning
confidence: 63%